Regulation of Child and Adolescent Employment in Alberta - Barnetson, Bob (Just Labour, 2009)
As part of a broader assessment of how well the Government of Alberta’s labour programming contributes to fair and, to a lesser degree, safe workplaces, this study examines how effectively the government enforces the Employment Standards Code provisions regulating child and adolescent employment. Enforcement strategies appear to emphasize softer forms of regulation and thereby create little disincentive for violations. Preliminary research into the employment levels of children (age 9-11) suggests over 11,000 children are employed, some perhaps illegally, and that further inquiry into their employment experiences is warranted.